Perspektif Pelaku Bisnis Perhotelan di D.I. Yogyakarta terhadap CSR - Adisty Ayu Apsari; Abdul Rohman (Jurnal Komunikasi)
The development of Corporate Social Responsibility (CSR) has been nourished by various practices undertaken by private entities. Hotel is one of business sectors that have acclaimed performing CSR, however, they raise critiques as it is mainly in the form of charities. It can be caused by either misconception of CSR, lacking of resources, or other factors involving in the spectrum. This study attempts to reveal definition of CSR and its decision making at the management level, and constraints in the program delivery. It finds that most of hotel participating in the study defines CSR as corporate philanthropy, perceives it as important at strategic management level, and sees insufficient time, money, and beneficiaries as major constraints.